Labor Unions and the Electoral Consequences of Trade Liberalization - Pedro Molina Ogeda; Emanuel Ornelas; Rodrigo R. Soares (Center for Economic Studies and ifo Institute (CESifo), 2021)
We show that the Brazilian trade liberalization in the early 1990s led to a permanent relative decline in the vote share of left-wing presidential candidates in the regions more affected by the tariff cuts. This happened even though the shock, implemented by a right-wing party, induced a contraction in manufacturing and formal employment in the more affected regions, and despite the left's identification with protectionist policies. To rationalize this response, we consider a new institutional channel for the political effects of trade shocks: the weakening of labor unions. We provide support for this mechanism in two steps. First, we show that union presence—proxied by the number of workers directly employed by unions, by union density, and by the number of union establishments—declined in regions that became more exposed to foreign competition. Second, we show that the negative effect of tariff reductions on the votes for the left was driven exclusively by political parties with historical links to unions. Furthermore, the impact of the trade liberalization on the vote share of these parties was significant only in regions that had unions operating before the reform. These findings are consistent with the hypothesis that tariff cuts reduced the vote share of the left partly through the weakening of labor unions. This institutional channel is fundamentally different from the individual-level responses, motivated by economic or identity concerns, that have been considered in the literature.
Keywords: F13; D72; J51; F16; F14; 330; trade shocks; elections; unions; Brazil